Developing a more comprehensive and expressive SOA governance framework - Hojaji, Fazilat; Shirazi, Mohammad Reza Ayatollazadeh (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
Many companies have adopted Service-Oriented Architecture (SOA) as an approach to improve agility and increase performance of system development. However, deploying SOA has been encountered with some challenges and problems such as service funding, service ownership and standards compliance for years. Therefore, to address SOA challenges, organizations require a comprehensive and applicable SOA governance framework to implement management and control mechanisms. A number of SOA governance frameworks have been proposed by researchers and practitioners. The scope and coverage of these frameworks differ extensively. Nevertheless, they do not completely document SOA processes, governance procedures and SOA roadmap, and also they do not cover all important elements of SOA governance. In this paper, in the process of proposing a new SOA governance framework, a set of important elements for a desired SOA governance framework have been proposed. Based on these elements, a more comprehensive and expressive framework is developed with focus on covering SOA governance elements and documenting SOA processes and activities, defining control as the policies and procedures embedded in each process and providing metrics and maturity model. The proposed framework is obtained by extending characteristics of COBIT framework to cover and support the SOA principles and requirements.